Adaptasi Ruang Berdasarkan Perilaku Penghuni Sub Komunal Rumah Instan Sederhana Sehat (RISHA), Semanggi, Surakarta - Fauzan Ali Ikhsan; Anita Dianingrum; Kusumaningdyah Nurul Handayani; Pratiwi Anjar Sari; Mohamad Muqoffa; Titis Srimuda Pitana (ARSITEKTURA, 2021)
Sub Communal RISHA is a pilot project from the central government in collaboration with the Surakarta City Government as a solution for structuring slum settlements in Surakarta. The RISHA method facilitates the construction and installation process due to the use of a modular precast system which is also more flexible and efficient both in terms of construction time and the use of construction materials. The purpose of this research is to identify the space adaptation of Sub Communal RISHA based on the behavior of residents. This research was conducted with a qualitative descriptive method. The research location is in the area of RW 06 Rusunawa Semanggi Surakarta and the time of data collection was carried out in the period May-August 2021. Primary data was taken with several techniques, observation and Forum Group Discussion (FGD) method. The analysis was carried out using data triangulation techniques. The use of this analysis technique aims to combine all data to produce accurate and comprehensive conclusions. The results showed that there are two adaptations carried out by the residents of Sub Communal RISHA, namely adaptation by adjustment and adaptation by reactions.